1998
DOI: 10.1111/j.1440-1827.1998.tb03946.x
|View full text |Cite
|
Sign up to set email alerts
|

Nodular mucinosis of the breast: Report of three cases

Abstract: Three cases of nodular mucinosis of the breast are presented. They occurred in one male and two female patients. The patients had no signs of Carney's syndrome. All lesions were located under the nipple. They were poorly circumscribed and unencapsulated. They were soft and had a gelatinous consistency and white color. No patient had any evidence of recurrence or metastasis 6 months, 3 years and 6 years, respectively, after the surgical excision. The mucinous tissue consisted of acid mucopolysaccharides, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 8 publications
0
34
0
Order By: Relevance
“…Practically, however, the lesions reported in the breast with diffuse myxoid stromal changes are: superficial angiomyxoma [9], nodular mucinosis (first reported as nerve sheath myxoma) [16,17], nodular fasciitis (myxoid variant) [18], neurofibroma (myxoid variant) [19,20], myofibrolastoma (myxoid variant) [21,22], myxofibrosarcoma [23], myxoid liposarcoma [24], and mucocele-like tumors [15]. A list of these lesions, including their main clinico-pathological features, is provided in Table 1.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Practically, however, the lesions reported in the breast with diffuse myxoid stromal changes are: superficial angiomyxoma [9], nodular mucinosis (first reported as nerve sheath myxoma) [16,17], nodular fasciitis (myxoid variant) [18], neurofibroma (myxoid variant) [19,20], myofibrolastoma (myxoid variant) [21,22], myxofibrosarcoma [23], myxoid liposarcoma [24], and mucocele-like tumors [15]. A list of these lesions, including their main clinico-pathological features, is provided in Table 1.…”
Section: Discussionmentioning
confidence: 98%
“…Unlike myxoma, it has a typical multilobular appearance both at gross and microscopic examination due to the presence of fibrous septa [1]. Nodular mucinosis typically occurs under the nipple, with poorly circumscribed margins due to the arrangement of myxoid stroma into small nodules [16,17]. Nodular fasciitis (myxoid variant) is a fibro-myofibroblastic pseudosarcomatous lesion with, at least focally, infiltrative margins, composed of spindle-shaped cells which are typically positive for α-smooth muscle actin [18,25].…”
Section: Discussionmentioning
confidence: 99%
“…Although the term was initially described by Michal et al [2], the first case had been reported under the name of "nerve sheath myxoma of the breast" by Wee et al [1]. It is distinct from widespread mucinous nodules that can be seen in the breast as a component of Carney complex syndrome, and always seen around the areola or nipple complex.…”
Section: Discussionmentioning
confidence: 99%
“…Usually the lesion has lobular configuration and consists of mucinous pools within the breast parenchyma without benign or malignant epithelial cell component. Breast ducts can be seen between the mucinous lobules but not within the pools [2]. Vessels and some benign-looking spindle stromal cells which may stain with smooth muscle actin (SMA), and CD68-positive histiocytes may also be seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation